2022
DOI: 10.3389/fnins.2021.807434
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Assessments in a Mouse Model of Congenital Blindness

Abstract: Previous studies have reported that visual impairment can affect the quality of life leading to mental health disorders. This study aimed to investigate associations between vision impairment, depression and anxiety using a mouse model of congenital blindness. We phenotyped 15 anophthalmic and 17 sighted adult mice in a battery of tests for anxiety and depression-like behaviors: open field test, elevated plus maze, coated test, splash test, and forced swim test. We found that: (1) Anxiety levels of the anophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…No differences between sighted and anophthalmic juvenile mice were observed otherwise in self-grooming, social sitting, and sitting-alone behaviors. Consistent with previous studies (Klein and Brown, 1969 ; Dyer and Weldon, 1975 ; Iura and Udo, 2014 ), we recently reported that congenitally blind mice exhibited an enhanced motivational level to explore a new environment, such as seen in the open-field, Elevated Plus Maze (EPM), and Forced Swim tests, compared to sighted controls (Bouguiyoud et al, 2022 ). The hyperactivity observed in blind mice when exploring a novel environment may reflect a compensatory mechanism by which the lack of visual information is counterbalanced by gathering and memorizing information from the physical world before it becomes familiar (Iura and Udo, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…No differences between sighted and anophthalmic juvenile mice were observed otherwise in self-grooming, social sitting, and sitting-alone behaviors. Consistent with previous studies (Klein and Brown, 1969 ; Dyer and Weldon, 1975 ; Iura and Udo, 2014 ), we recently reported that congenitally blind mice exhibited an enhanced motivational level to explore a new environment, such as seen in the open-field, Elevated Plus Maze (EPM), and Forced Swim tests, compared to sighted controls (Bouguiyoud et al, 2022 ). The hyperactivity observed in blind mice when exploring a novel environment may reflect a compensatory mechanism by which the lack of visual information is counterbalanced by gathering and memorizing information from the physical world before it becomes familiar (Iura and Udo, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…Numerous psychiatric mouse models have been developed to study anxiety and depression disorders. ,, Many of these models have successfully demonstrated translational validity in the study of human neuropathology and therapeutic intervention. As critical as these in vivo models are for the development of novel psychotherapeutic treatments, there has also been some skepticism in their application due to the more complicated cognitive and emotional spectrum inherent in human neuropsychology.…”
Section: Resultsmentioning
confidence: 99%
“…The hedonic response to stimuli can be measured through a sucrose preference test, as described by a previous study. After a 24-h period of food deprivation, the experimental animals were simultaneously provided with two bottles: one containing 1% sucrose solution and the other containing water. The intake amounts over a 24-h period were measured to analyze sucrose preference: sucrose intake (mL)/water intake (mL) + sucrose intake (mL) × 100.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were fixed 50 cm above the ground by attaching a fixation device to the tail tip. The movements of the animals during the last 5 min, following a 2 min adaptation, were recorded to analyze the immobility time, enabling the assessment of behavioral despair. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation